Nomogram for predicting prognosis of patients with metastatic melanoma after immunotherapy: A Chinese population–based analysis - Zhao, Jingjing; Li, Dandan; Xie, Songzuo; Deng, Xinpei; Wen, Xizhi; Li, Jingjing; Wu, Zhengrong; Yang, Xinyi; Li, Minxing; Tang, Yan; Zhang, Xiaoshi; Ding, Ya (Frontiers in Immunology, 2022)
Background:Previous studies indicated the evidence that baseline level of thyroid antibodies, thyroid status, serum lactate dehydrogenase (LDH) and M stage may influences the prognosis of advanced or metastatic melanoma patients treated with immune checkpoint inhibitors that targets programmed death receptor-1 (PD-1) or programmed death ligand 1 (PD-L1) which was reported that dramatic improvements in survival rates were observed, however, the presence of controversy has prevented consensus from being reached. Study objectives were to develop a nomogram to identify several prognostic factors in Chinese patients with metastatic melanoma receiving immunotherapy. Methods: This retrospective study included 231 patients from Sun Yat-sen University Cancer Center, patients were split into internal cohort (n=165) and external validation cohort (n=66). We developed a nomogram for the prediction of response and prognosis based on the level of serum thyroid peroxidase antibody (A-TPO), free T4 (FT4) and lactate dehydrogenase (LDH) levels that were measured at baseline of anti-PD-1 infusion. And the follow-up lasted at least until 5 years after the treatment or mortality. RECIST v1.1 was used to classify treatment responses. Results: Chi-square test showed that PD-1 antibody was more effective in melanoma patients with high level baseline FT4 or earlier M stage. A multivariate Cox analysis showed that baseline FT4 (P =0.009) , baseline A-TPO (P =0.016), LDH level (P = 0.013) and M stage (P <0.001) independently predicted OS in melanoma patients.The above factors are integrated and a prediction model is established: nomogram. Survival probability AUC values of 1-, 2- and 3-year in the training, internal validation and external validation showed the prognostic accuracy and clinical applicability of nomogram. (Training:0.714, 0.757 and 0.764; internal: 0.7171963, 0.756549 and 0.7651486; external: 0.748, 0.710 and 0.856). In addition, the OS of low-risk versus high-risk patients varied significantlys in both training groups(P < 0.0001) and external validation (P < 0.0012) cohorts, based on risk (total score > 142.65). Conclusions: According to this study, baseline biomarkers are associated with response to immunotherapy and prognosis among metastatic melanoma patients. Treatment regimens can be tailor-made based on these biomarkers.